Educator Evaluation Guidelines - Constance Baldwin; Latha Chandran; Maryellen Gusic (Association of American Medical Colleges, 2012)
Abstract Too often, educators are disadvantaged in the promotion and tenure process because their roles are not well understood by committees, and methods to evaluate educator performance have not been standardized. These educator evaluation guidelines contribute to the construction of a framework for the academic promotion and advancement of educators. The guidelines were designed to assist members of promotion committees in the evaluation of medical school faculty by a systematic, objective, and criterion-based process, and to help educators understand the elements of performance by which they are evaluated. To make the tool as accessible and usable as possible we avoided technical educational jargon, provided concrete indicators for each item, and illustrated items with copious examples. The guidelines include two tables with a total of 24 evaluation items distilled from our previously published, 36-item research tool for analysis of educator portfolios. That research tool was created by an iterative consensus development process and tested with live educator portfolios, so the items included in these guidelines have been well validated. The first table (19 items) is organized around five domains of educator performance: teaching, curriculum, advising/mentoring, educational leadership/administration, and learner assessment. The second table (five items) addresses the two components of scholarly activity: scholarly approach and educational scholarship. The five domains and two definitions of scholarly activity were confirmed by a consensus conference convened by the AAMC Group on Educational Affairs in 2009. Each domain is defined and elaborated with items for evaluation selected to capture quantity, quality, and impact of performance. For each evaluation item, several suggested indicators describe what kinds of evidence might earn credits for the educator and specific examples of high-quality performance are provided. Evaluation of educators is not well captured by numerical measures only. Items in the guidelines are appropriate for both quantitative and qualitative assessment; quantitative items are labeled. Despite the difficulty of objectively evaluating qualitative measures, some elements of educational practice are best assessed based on their adherence to accepted educational principles, rather than by being counted. Thus, the guidelines encourage an educator evaluation that is flexible and takes a broad perspective on performance. The guidelines avoid a prescriptive approach. They do not include a rating system, because each institution needs to develop its own scoring approach based on the value it places on specific educator activities. We have left room for institutions to decide how many areas of excellence are expected of a faculty member in each promotion track and at each rank. However, the included User's Manual discusses possible approaches to creating a rating system to accompany the 24-item evaluation tool.